2022
DOI: 10.3390/w14010082
|View full text |Cite
|
Sign up to set email alerts
|

Object-Based Multigrained Cascade Forest Method for Wetland Classification Using Sentinel-2 and Radarsat-2 Imagery

Abstract: The development of advanced and efficient methods for mapping and monitoring wetland regions is essential for wetland resources conservation, management, and sustainable development. Although remote sensing technology has been widely used for detecting wetlands information, it remains a challenge for wetlands classification due to the extremely complex spatial patterns and fuzzy boundaries. This study aims to implement a comprehensive and effective classification scheme for wetland land covers. To achieve this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Since two different types of satellite datasets are used to investigate the proposed Wet-GC model, in order to maintain the integrity and provide a logical comparison, these datasets are stacked and utilized for the rest of the algorithms employed here. For comparison purposes and to evaluate the efficiency of the Wet-GC, several models, including Random Forest (RF), Support Vector Machine (SVM), Extreme Gradient Boosting (XGB), and ResNet50 [64] were selected as efficient classifiers for wetland classification, as reported in [29], [34], [65], [66]. Based on experience reported in [3], [67], and trial and error, the optimum values for the parameters of RF, SVM, and XGB classifiers are defined and presented in Table VΙ.…”
Section: ) Wetland Classification By Well-known Modelsmentioning
confidence: 99%
“…Since two different types of satellite datasets are used to investigate the proposed Wet-GC model, in order to maintain the integrity and provide a logical comparison, these datasets are stacked and utilized for the rest of the algorithms employed here. For comparison purposes and to evaluate the efficiency of the Wet-GC, several models, including Random Forest (RF), Support Vector Machine (SVM), Extreme Gradient Boosting (XGB), and ResNet50 [64] were selected as efficient classifiers for wetland classification, as reported in [29], [34], [65], [66]. Based on experience reported in [3], [67], and trial and error, the optimum values for the parameters of RF, SVM, and XGB classifiers are defined and presented in Table VΙ.…”
Section: ) Wetland Classification By Well-known Modelsmentioning
confidence: 99%
“…Tian et al [16] used random forest to classify the vegetation of wetlands in arid areas of Xinjiang. L. F. Ruiz et al [17][18][19][20][21] used Sentinel-1 images to classify wetland types.…”
Section: Introductionmentioning
confidence: 99%
“…For all three groups of classification approaches, the spatial resolution of the satellite imagery, number of spectral bands, repetition time of the RS datasets, and complexity of the study area have direct effects on the precision of the final classified wetlands [11]. Overall, it has been frequently reported that using object-based classification techniques improves the accuracy of the classified map, particularly when using high-resolution RS datasets [8,12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%